Impact of Environmental Clauses of Regional Trade Agreements in the Pollution Levels - Fairlie Reinoso, Alan (2021)
Climate change and the impact of the economic model in the environment, forces the countries of the region to establish different tools and mechanisms to face its negative effects. For that reason, the environmental provisions of Regional Trade Agreements play a crucial role in guaranteeing environmental quality. This article estimates the impact of the environmental clauses of the regional trade agreements on the environmental pollution indicators of the partner exporting countries, especially in the Pacific Alliance.